Development, characterization and chemometric analysis of gluten-free granolas containing whole flour of pseudo-cereals new cultivars - doi: 10.4025/actascitechnol.v36i1.19195 - Souza, Aloisio Henrique Pereira; Gohara, Aline Kirie; Pagamunici, Lilian Maria; Visentainer, Jesui Vergílio; Souza, Nilson Evelázio; Matsushita, Makoto (Acta Scientiarum. Technology, 2014)
The goal of this study was the development, quimiometric analysis, physical-chemical, microbiological, nutritional, and sensory evaluation of gluten-free granolas containing quinoa, amaranth and linseed. Gluten fractions were not detected in the granola formulations prepared. The crude protein and total lipids contents ranged from 86.72 to 97.49 and 97.84 to 134.03 g kg-1 of food, respectively. The polyunsaturated/saturated and n-6: n-3 fatty acid ratios were 3:1. Calcium was the major mineral and the contents of trace minerals copper, iron, magnesium, manganese and zinc were over 10% of the dietary reference intake values. The granola color tended to light brown. The absence of Bacillus cereus, thermotolerant coliforms, coagulase positive staphylococcus, and Salmonella sp. ensured the product safety. All the granola formulations had good sensory acceptance and high purchase intent. The gluten-free granola formulations had good physical-chemical, sensory and nutritional quality. The use of chemometric analysis enabled to distinguish the samples with respect to their fatty acid composition, minerals content and sensory aspects.